Sevoflurane Insufflation Technique in Retinopathy of Prematurity Patients Underwent Intraocular Laser Photocoagulation: A Serial Case Report - Muhamad Adli; Irawati, Dian; Fitri Yadi, Dedi (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2024)
Introduction: Retinopathy of Prematurity (ROP) is a developmental abnormality of the retina and vitreous due to abnormal angiogenesis. The anesthetic considerations in the preterm neonate were based on the physiological immaturity of the various organ systems, associated congenital disorders, which may result in poor tolerance to anesthetic drugs, and also considerations regarding the use of high oxygen concentrations. Case Illustration: We are reporting six cases of ROP patients who underwent intraocular laser photocoagulation under Volatile Induction and Maintenance Anesthesia (VIMA) using a nasal cannula. The youngest patient at the time of the procedure was 32 weeks postmenstrual age, and the oldest patient was 36 weeks postmenstrual age, with the lowest weight of 1480 grams and the highest weight of 2770 grams. A gas mixture of oxygen, nitrous oxide, and 3-5 vol% sevoflurane was delivered through a nasal cannula delivered from an anesthesia machine for anesthesia induction and maintenance throughout the procedure. The anesthesia effect was achieved less than five minutes after gas mixture delivery in all patients. Five of six patients showed satisfactory results without any serious adverse effects during and after the procedures, and one of the patients was intubated due to repeated apnea and conversion of the surgical procedure from intraocular laser photocoagulation to vitrectomy. There was no adverse event observed after the procedure. Conclusion: The Effective induction and maintenance of anesthesia achieved through sevoflurane insufflation via nasal cannula suggest its viability as a practical and opiod-free alternative for volatile induction and maintenance anesthesia in pediatric procedures.